Bonding in PdH2 and Pd2H2 systems adsorbed on carbon nanotubes: Implications for hydrogen storage - López Corral, Ignacio (2014)
This work presents a bonding study of hydrogen adsorption processes on palladium decorated carbon nanotubes by using the density functional theory (DFT). First, we considered simple decoration models involving single palladium atoms or palladium dimers, and then we analyzed the adsorption of several molecular and dissociated hydrogen coordination structures, including Kubas-type complexes. In all cases we computed the energy, bonding and electronic structure for the different nanotube-supported hydrogen–palladium systems. Our results show that Pd(H2) and Pd2(H2) complexes with relaxed but not dissociated H–H bonds are the most stable adsorbed systems. The role of s, p and d orbitals on the bonding mechanism for all adsorbates and substrates was also addressed. We found intermolecular donor–acceptor C–Pd and Pd–H delocalizations after adsorption. We also studied the palladium clustering effect on the hydrogen uptake based on Kubas-type bonding.